Towards the rational design of a next-generation dendritic cell vaccine for cancer immunotherapy - Bravo, M; Davies, TJ; Fairchild, PJ (Bioinsights Publishing Ltd, 2021)
As professional antigen presenting cells (APCs) capable of eliciting primary immune responses among naïve T cells, dendritic cells (DCs) offer an attractive target for immune intervention. While some strategies for vaccination have sought to deliver antigens direct to DCs in vivo, others have pulsed DCs with target antigens ex vivo prior to administration. Indeed, numerous clinical studies of cancer immunotherapy have been conducted over the past two decades based on this approach, most of them benefitting from the ease with which DCs may be differentiated in vitro from the peripheral blood monocytes of individual patients. Nevertheless, while therapies exploiting monocyte-derived DCs (moDCs) have been shown to be safe, clinical outcomes have been disappointing, efficacy having been limited by factors including the type of DCs used and the source of tumor antigens. Here we review recent developments in identifying DC subsets with more favorable properties for use in cancer vaccination, with particular emphasis on CD141+ DCs capable of antigen cross-presentation and discuss alternative sources, such as induced pluripotent stem cells (iPSCs), amenable to manufacture at scale. Furthermore, we assess how different sources of tumor antigens may complement this approach for the design of next generation DC vaccines.